Towards a community of practice for climate security and environmental peacebuilding in Mindanao - Medina, Leonardo; Savelli, Adam; Jaquet, Stéphanie; Torres, Mark; Arcede, Jayrold; Hellin, Jon; Pacillo, Grazia (2023)
In combination with political, cultural, and economic factors, issues related to environmental resources and the management of land have played a crucial role in driving conflict in Mindanao. Climatic stressors and shocks are altering food, land, and water systems, and driving important socioeconomic challenges for food security and the stability of rural livelihoods across the Philippines. Although climate change and environmental degradation are altering food, land, and water systems throughout the Philippines, social groups experience these effects differently, at times reinforcing patterns of marginalisation and inequality. As such, environmental and climatic threats to livelihoods and access to resources can compound existing drivers of conflict. At the same time, societal efforts to increase resilience in the face of climate threats can serve as an entry point to protect the livelihoods of conflict-affected populations, foster engagement and trust between conflictive parties, and strengthen the relation between states and societies. If planned accordingly, climate action can indeed act as an instrument for peace. This workshop brought together 24 Philippine stakeholders from humanitarian, development, climate and peace sectors to explore opportunities for climate change adaptation to contribute to ongoing sustainable peacebuilding efforts in Mindanao. The workshop was carried out in person throughout 3 days of extensive engagement and dialogue amongst government representatives, NGOs, international organisations, and research institutes. Participants jointly determined three conflict lines which are most prevalent in Mindanao—identity-, politically-, and resource-driven conflicts—before identifying the main drivers of conflict for each, and, in turn, identifying potential entry points for climate adaptation efforts to contribute to sustainable peacebuilding in Mindanao. An agreement was also made to establish a Community of Practice between educational, peacebuilding, and research organizations to focus on four priority areas of action: evidence, programming, policy and governance, and education.